2019
DOI: 10.1007/s10877-019-00415-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological abnormalities in patients admitted with acute exacerbation of COPD: an observational study with continuous monitoring

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Heart rates >85 bpm or increases in heart rates by 10-15 bpm compared to baseline were reported during an acute exacerbation (49). Respiratory rates >24 breaths per min, with shortened expiratory time leading to gas trapping, have been consistently reported in most studies conducted in hospitalized patients (51,53), whereas respiratory rates of 18-20 breaths per min were documented in patients receiving outpatient care (53). The panel reached consensus that a heart rate <95 bpm and a respiratory rate <24 breaths per min could help separate mild from moderate ECOPD.…”
Section: Respiratory and Heart Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Heart rates >85 bpm or increases in heart rates by 10-15 bpm compared to baseline were reported during an acute exacerbation (49). Respiratory rates >24 breaths per min, with shortened expiratory time leading to gas trapping, have been consistently reported in most studies conducted in hospitalized patients (51,53), whereas respiratory rates of 18-20 breaths per min were documented in patients receiving outpatient care (53). The panel reached consensus that a heart rate <95 bpm and a respiratory rate <24 breaths per min could help separate mild from moderate ECOPD.…”
Section: Respiratory and Heart Ratementioning
confidence: 99%
“…Studies have shown that both heart rate and respiratory rate increase in the days preceding, during and following ECOPD (30,31,47,48), and are measurable by widely available noninvasive methods offering a window to the severity of the episodes (48)(49)(50)(51).…”
Section: Respiratory and Heart Ratementioning
confidence: 99%
“…Continuous wireless monitoring may enable high‐frequency monitoring of physiological status on general wards outside the intensive care (ICU) or post‐anesthesia care unit (PACU) without restricting early postoperative mobilization or requesting unrealistic staffing. Ongoing technological research on general wards has consistently shown continuous monitoring to be superior to track and trigger systems in detecting abnormal vital signs 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…Indwelling endotracheal intubation for mechanical ventilation can effectively dilate the airway of spastic obstruction, reduce carbon dioxide retention, improve the state of ventilation and oxygenation, and promote the rapid improvement of the patients' conditions [30]. Although invasive mechanical ventilation is the primary approach of treatment for the patients with ARF in a state of unconsciousness, it does not work well to the patients with COPD because the functions of their airway structural defense barrier would be attenuated with a higher risk of bacterial infection due to the existence of irreversible airway obstruction lesions, reduction of mucosal surface cilia, mucosal hyperemia and edema, and mucous glandular cell hyperplasia and hypertrophy [31,32]. Apart from that, since the patients with COPD are also affected by long-term malnutrition, unsatisfactory development of respiratory muscles, and abatement of physical strength, it is more likely for them to become heavily dependent on ventilators so that there is much more difficulty in taking away the assisted respiratory equipment after invasive mechanical ventilation support treatment.…”
Section: Discussionmentioning
confidence: 99%